4CPS-098 Influence of pharmacological interactions in hepatitis C treatment selection in opiate-dependent patients. (March 2019) - Zurutuza, A; Carmona, MP; García, D; Landa, J; Gonzalez, T; Pascual, P; Lopez, G; Lombera, L; Ripa, C; Bachiller, MP; Gayan, MJ
Abstract : Background: The therapeutic strategy for chronic hepatitis C (CHC) in our health system established that in mono- or co-infected HCV/HIV patients in whom prioritised therapy with glecaprevir/pibrentasvir is contraindicated, their chronic medication (CM) will be changed and/or an alternative therapy for HCV will be used: sofosbubir/velpatasvir (+7% cost per patient) or elbasvir/grazoprevir (+64% cost per patient). Purpose: To analyse the influence of pharmacological interactions in the selection of HCV treatment in opiate-dependent patients. Material and methods: All treatments started in a Mental Health Network (which opiate-dependent patients attend) from 1 January 2018 to 31 August 2018 were analysed. Prior to the approval of hepatitis C treatment by the CHC committee, the pharmacist reviewed the treatment and looked for possible pharmacological interactions of the HCV prioritised therapy with the CM. If there was a significant interaction, the pharmacist recommended either to change/stop the CM or to choose an alternative HCV treatment. Results: Approved treatments by the CHC committee: 96. Completed treatments: 73, 98% monoinfected. HCV genotype: 1a: 31 (42%), 3: 22 (30%), 4: 11 (15%), 1b: seven (10%) and 2: two (3%). Forty-seven (64%) patients were ≤F3, 21 (29%) F4 and five (7%) were unknown. 64/73 (88%) patients were treated with glecaprevir/pibrentasvir. A CM change was needed in 14/64 (22%) patients: to avoid metamizole, delay proton-pump inhibitor administration time, to switch to another statin and stop oxcarbazepine. Only 9/73 patients (12%) received a non-prioritised treatment with sofosbuvir/velpatasvir. In eight of them due to interactions with their CM: antipsychotics (five), HIV protease inhibitor (one), anti-platelet (one) and ethinylestradiol (one). In another patient the reason was that he was Child-Pugh B. The sustained viral response is available only in 20% of patients, so the effectiveness has been measured as viral response at the end of treatment (VRE), being 96% (70/73) up to date. Three patients are pending to be determined. Conclusion: The review of pharmacological interactions has allowed the treating of 88% of patients with the prioritised therapy, with an effectiveness in VRE of 96%, according to the results of the clinical trials. The pharmacological interactions evaluation and pharmaceutical interventions optimize the risk benefit ratio and contribute to the efficient use of HCV therapies. References and/or acknowledgements: No acknowledgements. No conflict of interest.